*An approach to ship position estimation and clutter suppression based on GEO satellite/airborne bistatic sar with a multi-receive antenna. Issue 9 (2nd September 2018) - Jiang, Yicheng; Lian, Meng
ABSTRACT: Geosynchronous spaceborne-airborne bistatic synthetic aperture radar (GEO SA-Bi SAR), which employs a geosynchronous orbit (GEO) satellite as a transmitter and an aeroplane that works on the 'receive-only' mode as a receiver, is distinct from general bistatic synthetic aperture radar (SAR) systems. In this paper, a GEO SA-Bi SAR system with multi-receive antenna is consider for marine surveillance. First, ship position is estimated in the configuration of GEO SA-Bi SAR with multi-receive antenna, using maximum likelihood (ML) method. Then, according to the estimation result, sea clutter in the signal of a moving point target is suppressed by adaptive beamforming (ABF). Moreover, the performance of our method is analysed and studied in terms of the point target imaging. The simulation results demonstrate the correctness and effectiveness of the proposed method.